A dissertation on adolescent compliance with oral hygiene instruction during orthodontic treatment - Faruk, SM Omar; Hossain, Md Zakir (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2015)
Objectives: To determine the level of compliance with Oral Hygiene Instruction ( OHI) of 12 to 18 years old adolescent patient receiving orthodontic treatment at Dhaka Dental College and Hospital. Materials and Methods : In this descriptive observational study, a total number of 100 patients (37 boys & 63 girls) were selected (with convenient sampling) from Orthodontics and Dentofacial Orthopedics Department in Dhaka Dental College & Hospital. As the number of female patient is higher than that of male patient at Orthodontics and Dentofacial Orthopedics Department in Dhaka Dental College & Hospital and the samples were selected with convenient sampling, the number of female patient was higher in this study. Results: This was an observational study conducted among 100 patients in the department of Orthodontics and Dentofacial Orthopedics, Dhaka Dental College and Hospital. The result of this study indicates that after five month of insertion of orthodontic appliance, 76% patients were good complier with Oral Hygiene instruction (OHI). Conclusion: The insertion of orthodontic appliances can result in changes in the oral environment, such as causing higher concentration of acid-producing bacteria due to the difficulty of performing oral hygiene after the insertion of appliance. Orthodontic appliances can also be associated with white spots, enamel decalcification, periodontal breakdown, and development of carious lesions. Continual plaque build-up may thus jeopardize the continuity of orthodontic treatment and the achievement of successful treatment outcome. So it is very important to give Oral Hygiene Instruction (OHI) at the commencement of orthodontic treatment and close supervision of the patient during treatment. Ban J Orthod & Dentofac Orthop, April 2013; Vol-3, No.2